Adverse events with the use of hyaluronic acid in HOF – A narrative literature review (Research, Society and Development, 2023)
With the increase in people looking for aesthetic procedures, especially facial procedures, numerous techniques and materials have emerged in the Orofacial Harmonization market. Among the materials, filling with the use of injectable hyaluronic acid stands out. Being a natural substance found in the human body itself, its applicability has gained scale and supporters. Due to its short half-life, purification and cross-linking techniques were added by the industry, providing products with greater density, purity and durability. Inevitably, the scalar increase in the use of this substance has proportionally increased the number of reports of adverse effects. Among the causes of these adversities stand out the inability of operators, incorrect application techniques, lack of knowledge of the products, in addition to organic factors inherent to the individual. Adverse effects are classified as early and late, the most common being: edema, erythema, ecchymosis, hematoma, infection, nodules, necrosis, vascular complications, granulomas, allergic reactions and scars. Cryotherapy, compress, use of antibiotics, systemic and intralesional corticoids, in addition to hyaluronidase, are part of the range of procedures that are part of the treatment to combat these adverse effects.